2011
DOI: 10.1080/0194262x.2011.626341
|View full text |Cite
|
Sign up to set email alerts
|

What Do I Do in an Emergency? The Role of Public Libraries in Providing Information During Times of Crisis

Abstract: During times of crisis, whether they are caused by a potential pandemic such as the 2009 H1N1 virus infections, bioterrorism threats, or natural disasters, people seek answers to questions about the nature of the threats and how to respond to them. Libraries need to leverage their position as a primary source of trustworthy information by providing quick and easy access to those looking for credible information about what to do in an emergency. This article will present an overview of public libraries' respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 30 publications
1
36
0
3
Order By: Relevance
“…If little else is learned from the recent experience of Elliot Lake Public Library, it is imperative to be aware of the fact that, in order to be the most effective, any disaster management plan must consider not only collection preservation and safety concerns but also a clear and actionable plan to ensure the uninterrupted availability of postdisaster information services (Bishop and Veil 2013;Dickerson 2007;Hamilton 2011;Jaeger et al 2006;McClure et al 2009;Wessling 2000;Zach 2011;Zach and McKnight 2010).…”
Section: Assuming a Leadership Role In Disaster Managementmentioning
confidence: 97%
See 1 more Smart Citation
“…If little else is learned from the recent experience of Elliot Lake Public Library, it is imperative to be aware of the fact that, in order to be the most effective, any disaster management plan must consider not only collection preservation and safety concerns but also a clear and actionable plan to ensure the uninterrupted availability of postdisaster information services (Bishop and Veil 2013;Dickerson 2007;Hamilton 2011;Jaeger et al 2006;McClure et al 2009;Wessling 2000;Zach 2011;Zach and McKnight 2010).…”
Section: Assuming a Leadership Role In Disaster Managementmentioning
confidence: 97%
“…Should libraries maintain their largely reactionary approach to disasters, or should they adopt a more proactive role that considers the opportunities that a disaster-no matter how horrific-may provide for improving community engagement as well as library services (Bishop and Veil 2013;Dickerson 2007;Hamilton 2011;Jaeger et al 2006;McClure et al 2009;Wessling 2000;Zach 2011;Zach and McKnight 2010)? Disasters present an unprecedented opportunity for libraries to highlight their value to the community as professional providers of reliable information and communication services that may otherwise be unavailable to individuals during and following a disaster.…”
mentioning
confidence: 97%
“…In an article about Ontario public libraries’ response to SARS information inquiries, Harris et al [69] suggest that many public library staff may be unprepared to provide such information. Similarly, in a review of public libraries’ responses to the 2009 H1N1 epidemic, Zach [70] notes that about a month after the first case of H1N1 was diagnosed in the US, only 15 out of 50 public library systems in the most populated US cities linked to CDC or other e-government information about H1N1. Overall, Zach [70] concluded that, despite some notable efforts, issuing risk alerts and providing epidemics preparedness information was not a priority for public libraries.…”
Section: Providing Health Information Relevant To Disasters and Emmentioning
confidence: 99%
“…Similarly, in a review of public libraries’ responses to the 2009 H1N1 epidemic, Zach [70] notes that about a month after the first case of H1N1 was diagnosed in the US, only 15 out of 50 public library systems in the most populated US cities linked to CDC or other e-government information about H1N1. Overall, Zach [70] concluded that, despite some notable efforts, issuing risk alerts and providing epidemics preparedness information was not a priority for public libraries. On the other hand, while comfort level with specialized information provision will always differ by setting and topic, there are also responses of active engagement.…”
Section: Providing Health Information Relevant To Disasters and Emmentioning
confidence: 99%
“…These statistics are key because FEMA aid forms can only be completed online and require certain types of software (e.g., web browsers) and technical know‐how. After a natural disaster, the need for e‐government services is heightened, explaining why public libraries have been identified as a centralized hub for connectivity following disasters …”
Section: Introductionmentioning
confidence: 99%